Las redes sociales como fenómeno condicionante en la conducta social de los adolescentes de la Unidad Educativa Eugenio Espejo del Cantón Babahoyo, Provincia de los Ríos - Alvarado Pazmiño, Evelin (2015)
Education Unit Eugenio Espejo Canton Babahoyo is an institution whose main objective is the proper preparation of the individual in the field of scientific research seeking to maintain quality standards in knowledge and skills developed in students, as reflected in its Mission. These high standards to which they refer, are analyzed in this research, linking it exclusively to the technological training of students, analyzing the domain of teenagers level using social networks for training in social development. Surveys, interviews and direct observation are the instruments used for scientific analysis required by the issues raised around social networks who have this education sector in the province and the country